2022
DOI: 10.1186/s12890-022-02053-4
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death following small cell lung cancer diagnosis: a population-based analysis

Abstract: Purpose To examine the distribution of causes of death (CODs) in patients with small cell lung cancer (SCLC). Methods Patients diagnosed with SCLC were identified from the Surveillance, Epidemiology, and End Results Program database during 2004–2015. Standardized mortality rates (SMRs) were performed for each COD to present changes in risk for a particular COD following SCLC diagnosis. Results A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…We have demonstrated that heart disease was the most common non-cancer COD in patients with GC, which is in line with the reports from other cancers [ 14 17 ]. It could be partly explained by the primacy of cardiovascular mortality in the United States [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…We have demonstrated that heart disease was the most common non-cancer COD in patients with GC, which is in line with the reports from other cancers [ 14 17 ]. It could be partly explained by the primacy of cardiovascular mortality in the United States [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Cancer and heart disease are two main causes of death worldwide 9 . Previous study assessing causes of death in cancer patients pointed to an increased risk of cardiovascular disease in cancer patients 10 , 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, the proportion of non cancer death have changed over time, cardiovascular death (CVD) has consistently dominated. Cancer and heart disease are two main causes of death worldwide 9 . Previous study assessing causes of death in cancer patients pointed to an increased risk of cardiovascular disease in cancer patients 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Site codes C34.0-C34.3 and histological codes: 8002/3, 8041/3, 8042/3, 8043/3, 8044/3, and 8045/3, derived from the World Health Organization International Classification of Diseases of Oncology, Third Revision (ICD-O-3), served as the criteria for diagnosing SCLC and extracting relevant data. [17] Due to the absence of recorded metastasis-related information, including bone, brain, liver, and lung data, in the SEER database prior to 2010, this study primarily focused on gathering data from SCLC patients diagnosed between 2010 and 2015. Additionally, it is worth noting that there is no universally agreed-upon definition of “elderly.” However, taking into account insights from previous literature, this study establishes that “elderly SCLC patients” specifically refers to individuals who are aged ≥ 65 years.…”
Section: Methodsmentioning
confidence: 99%